2018
DOI: 10.26714/jsm.1.1.2018.59-63
|View full text |Cite
|
Sign up to set email alerts
|

Pemberdayaan Masyarakat sebagai Upaya Deteksi Dini Faktor Risiko Hipertensi

Abstract: AbstrakHipertensi masih merupakan masalah kesehatan yang penting. Prevalensi hipertensi nasional di Daerah Istimewa Yogyakarta (DIY) sebesar 35,8% dengan proporsi kasus hipertensi yang telah didiagnosis oleh tenaga kesehatan sebesar 24%. Hal ini berarti bahwa masih ada 76,0% kasus hipertensi di masyarakat yang belum terdiagnosis. Tingginya angka insidensi hipertensi di propinsi DIY tersebut turut mempengaruhi insidensi penyakit ini di kabupaten Bantul. Pola makan yang tidak sehat dan kurang terjaga, perilaku m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…CHWs can help with adherence to treatment in rural communities by giving social support [ 24 , 25 ]. Several documents reported that knowledge and skills of CHWs can be improved by comprehensive health education programs, training in communication, and usage of equipment and involvement of different stakeholders (for example primary healthcare staff) [ 21 – 23 , 26 – 36 , 41 , 66 , 72 , 80 , 86 – 88 ]. Related to this, support given by CHWs to community members, was the most dominant factor in the utilization of community-based interventions by community members [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…CHWs can help with adherence to treatment in rural communities by giving social support [ 24 , 25 ]. Several documents reported that knowledge and skills of CHWs can be improved by comprehensive health education programs, training in communication, and usage of equipment and involvement of different stakeholders (for example primary healthcare staff) [ 21 – 23 , 26 – 36 , 41 , 66 , 72 , 80 , 86 – 88 ]. Related to this, support given by CHWs to community members, was the most dominant factor in the utilization of community-based interventions by community members [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…10,13 Obesity is often found together with hypertension, DM, and hypertriglyceridemia cases. [12][13][14] In addition, obesity can increase total cholesterol and LDL cholesterol levels. The risk of CHD can increase if bodyweight starts to exceed 20% of ideal body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Penyuluhan secara langsung menjadi salah satu bentuk intervensi yang dilakukan karena masyarakat akan semakin mengenali penyakit ini. Penyuluhan tentang hipertensi dapat meningkatkan tingkat pengetahuan terutama bagi para lansia yang sebelumnya memiliki tingkat pengetahuan yang rendah [18][19][20].…”
Section: Hasil Dan Pembahasanunclassified